Institutions In Legal Systems As Embodiments Of Legal Purposes - Derita Prapti Rahayu; Faisal Faisal; Tony Tony (Faculty of Law, University of Mataram, 2019)
The statement that human life in society is governed by law. The law referred to here is the law known in the Regulations of State product legislation, established by the authorities, socialized through books, books and writings, not understood as the law that lives in society as a social construction even those that are thus only classified as social norms. The presence of law in the community agrees to integrate and coordinate interests that can conflict with each other that are integrated in order to be able to strengthen as little as possible. Organizing those interests is carried out with those interests and interests. The law that discusses this is a community-made law that contains the daily knowledge of each individual member of the community as a starting point for the birth of a social order.